GROWTH RESPONSES OF FRY OF COMMON CARP AND MOURALA TO DIFFERENT ABSOLUTE SPACE FACTORS - DATTA, SUBHENDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The influence of absolute space factor on growth performance of common carp (Cyprinus carpio) and mourala (Amblypharyngodon mola) that differ in their innate growth criterion was examined. Fifteen simulated pond systems that differ in absolute space by 7-fold (1.27, 2.86, 4.50, 6.20 and 9.11m) were used for both the test fishes for 90-day grow-out period. The pond fertilization and relative stocking density remained same (10/mi) for both the species and for all tanks. Examination of average weight in common carp revealed that large and Small fishes were skewed towards large and small tanks respectively. The average weight of common carp, at harvest, were significantly higher in largest tank than in the smallest one (p < 005. whereas spatial growth differences in mourala were not significant (p > 0.05). This suggests that the absolute sapace and food in the smallest tank did not act as stressor for mourala growth but clearly limited the growth of common carp. The amplitude of diurnal variations of dissolved oxygen of water acted as stressor in small tank but not in large tanks. It is proposed that large tanks provided not only more space but also provided more food produced as a result of interactions between water area and complex physico-chemical dynamics of water. It is also possible that the dispersion of fish metabolites or shift in metabolite dependent micro-niche caused by free movement of fish in larger tanks was perhaps responsible for enhanced fish growth mediated through better water quality and higher primary production of phytoplankton.